Indigenous health in the Arctic:an overview of the circumpolar Inuit population - Bjerregaard, Peter; Young, T Kue; Dewailly, Eric; Ebbesson, Sven O E (Scandinavian Journal of Public Health, 2004)
The health of the Inuit has undergone substantial changes over the past five centuries, as a result of social, cultural, and economic changes brought about by interactions with Europeans. This process was accelerated considerably in the second half of the twentieth century. The incidence of infectious diseases has declined considerably but is still high compared with Western societies. Chronic diseases such as diabetes and cardiovascular disease are on the increase, while accidents, suicides, violence, and substance abuse are of major importance for the pattern of ill health in most Inuit communities. Lifestyle changes, social change, and changes in society and the environment are major determinants of health among the Inuit.